The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/s19081864
|View full text |Cite
|
Sign up to set email alerts
|

Open Database for Accurate Upper-Limb Intent Detection Using Electromyography and Reliable Extreme Learning Machines

Abstract: Surface Electromyography (sEMG) signal processing has a disruptive technology potential to enable a natural human interface with artificial limbs and assistive devices. However, this biosignal real-time control interface still presents several restrictions such as control limitations due to a lack of reliable signal prediction and standards for signal processing among research groups. Our paper aims to present and validate our sEMG database through the signal classification performed by the reliable forms of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 36 publications
(68 reference statements)
0
24
1
Order By: Relevance
“…On these data, Palermo et al [11] reached an inter-session accuracy of 25.4% by feeding Wave Length to a Random Forest. Cene et al [16] successfully employed Extreme Learning Machines (ELMs) to raise this intersession accuracy to 41.8%. It is worth to notice that the reason why the accuracy reached on the NinaPro DB6 is much lower than the one reached on other datasets with a similar number of classes and sensors, is that the hand movements of NinaPro DB6 are all grasps, thus much less diverse and discernable than the gestures in ordinary datasets.…”
Section: B Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…On these data, Palermo et al [11] reached an inter-session accuracy of 25.4% by feeding Wave Length to a Random Forest. Cene et al [16] successfully employed Extreme Learning Machines (ELMs) to raise this intersession accuracy to 41.8%. It is worth to notice that the reason why the accuracy reached on the NinaPro DB6 is much lower than the one reached on other datasets with a similar number of classes and sensors, is that the hand movements of NinaPro DB6 are all grasps, thus much less diverse and discernable than the gestures in ordinary datasets.…”
Section: B Related Workmentioning
confidence: 99%
“…On the Unibo-INAIL dataset, Milosevic et al [10] showed that multi-posture and multi-day training improve intersession generalization. A Radial Basis Function kernel SVM (RBF-SVM) applied on 4-channel single samples of the RMS signal yielded an intra-session recognition accuracy higher than 90%, with an inter-session accuracy drop up to 20% (a value similar to [11], [16]). The aforementioned approaches showed the major limitation of classical ML: it strongly relies on domain-specific knowledge and hand-crafted features, limiting the capability to generalize over time.…”
Section: B Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…ELM is a feed forward neural network raised by professor Guang-Bin Huang [45], with a single input layer, a hidden layer, and an output layer. In most cases, the input weights and hidden nodes are randomly assigned, and the output weights are directly calculated by the least square method in just a single step.…”
Section: Pattern Recognition Methodsmentioning
confidence: 99%